DA MATA AO CENTRO: Lideranças Femininas e Quebra de Coco Babaçu na Amazônia Maranhense - FERREIRA, Bianca Silva (2024)
This research aims to investigate and analyze the trajectories of women coconut breakers from the villages of Petrolina, São Félix and Coquelândia, located on Estrada do Arroz, rural area of the city of Imperatriz – MA. Highlighting how the breaking of babassu coconuts and the conflicts arising from this activity led to women's leading role in the struggle to continue performing this work. We highlighted that the need to continue coconut breaking was important for the formation of social and political mobilization, that we collaborated so that coconut breakers were recognized and recognized as safe to fight. All work is guided with the following question as a reference: how is the need to defend access to palm trees, against the various attempts at exclusion over the years by different external agents, distributed by their social and political protagonism? We use oral history as a method, and as a research source we use existing bibliographies on the topic, we also use the women's point of view as a methodological resource through conversations, participation in meetings and interviews. We present the stories of resistance, through the experience told, highlighting this as an important point in the construction of the memory of the breakers that allowed us to understand the construction of their identities as breakers and leaders, by exposing their experiences as women transforming experiences into language (Alberti 2006, 2013). As a theoretical basis, authors who depart from a decolonial perspective were used to think about work and its relationships, such as Aníbal Quijano (2005), Enrique Dussel (2005), Marcelo Rosa (2014); Patricia Hill Collins (2019) and bell hooks (2019) who help us think about women's place in society as well as the importance of self-definition as a strategy for emancipation. Concepts related to peasant and popular feminism are thought through the collaboration of Calaça, Conte and Cinelli (2018). We also discuss the unsubmissive knowledge of these women, built from existence and the constant struggle against the continuous flow of power relations that arise from colonialism, using as a basis for analysis the authors Ângela Figueiredo (2020), Donna Haraway (2009), Maria Lugones (2014) and Lélia Gonzalez (1983, 1988 and 2020). In view of the proven sources, it is clear that the women breakers understand themselves as subjects of transformation and that working with babassu is an important element in the process of building their identities, which is permeated by the struggles that made them who they are. Thus, the subjectivity of being broken for these women began to make sense when they understood that they were trying to make them, and their knowledge, cease to exist. In this way, the possibilities of information resulting from this research allowed us to understand the process of building the knowledge that forms these leaders, as well as their self-preservation strategies, their work relationships and sociability.